Education in Border Areas: How to Fulfil the Right to Education of the Community on Lemukutan Island - Muhammad Hendri Nuryadi; Pipit Widiatmaka; Norhafiza Mohd Hed; Abdurrahman Abdurrahman (AL-ISHLAH: Jurnal Pendidikan, 2025)
The right to education in disadvantaged and remote areas is essential for fostering human development, reducing social inequality, and improving long-term economic outcomes. However, geographic isolation often leads to unequal access to educational resources. This study investigates the condition of education and the fulfillment of the right to education in Lemukutan Island, a border region in West Kalimantan, Indonesia. A qualitative descriptive approach was employed to explore the educational landscape on Lemukutan Island. Data were collected through in-depth interviews, direct observations, and document analysis. Informants included local residents, students, and school personnel. Data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. Findings revealed that access to education on Lemukutan Island is severely limited. The island only has one early childhood education center (PAUD), one elementary school, one junior high school, and no senior high school (SMA/SMK). Educational infrastructure is in poor condition, particularly at the junior high school level, where buildings are physically damaged and lack basic amenities. Students must travel 2–3 hours by sea and land to access high school education, contributing to a low level of educational attainment in the community. The study highlights the urgent need to improve infrastructure, ensure equitable distribution of qualified teachers, and provide locally relevant curricula. Addressing these issues is critical for fulfilling the educational rights of border communities and enhancing their human resource development.